ANALISIS KETERAMPILAN MAHASISWA PENDIDIKAN IPA DALAM MELAKUKAN PRAKTIKUM DAN BERKOLABORASI - Nurwahidah, Indri; Sari, Dwi Septiana (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
Prospective science teacher students must be able to carry out practicum well to deliver fun learning through experiments, as well as develop the ability to collaborate. The purpose of this study is to analyze student skills in conducting practicum and collaborating after COVID-19. This type of research is descriptive qualitative research and is carried out in the even semester of 2021-2022. Observations were made to obtain an overview of the skills of Ivet University Science Education students in carrying out practicum. The results showed that the average value of students in terms of (1) time effectiveness during practicum was 91.67; (2) skills in carrying out experiments of 87.50; (3) group dynamics of 81.25; (4) seriousness in observing the experiment, namely 77.08; (5) preparation and (6) cleanliness of practicum tools with a score of 75; (7) skills in the preparation of tools and materials, namely 70.83; and (8) leadership with a score of 66.67. Based on the results of the study, it can be concluded that students' skills in conducting practicum and collaborating are generally good, but leadership aspects and skills in preparing tools and materials still need to be improved.